Bezpieczeństwo energetyczne Polski = Energy safety of Poland - Ziembicki, Piotr; Nowak, Teresa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The publication presents problems related to energy safety of Poland. It was characterized Polish energy mix, and presented the state of the Polish energy sector indicating the basic problems of the power subsystem, as well as heating subsystem.
Keywords: bezpieczeństwo energetyczne; energia odnawialna; ciepłownictwo; mix energetyczny; energy safety; renewable energy; heating industry; energy mix